2006
DOI: 10.1086/506320
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes of Photospheric Magnetic Fields around Flaring Magnetic Neutral Lines

Abstract: In this paper we study the short-term evolution of magnetic fields associated with five flares in -sunspots. We concentrate on the analysis of the magnetic gradient along the flaring neutral lines (NLs). Obvious changes of the magnetic gradient occurred immediately and rapidly following the onset of each flare. A rapid gradient increase was found to be associated with three events, while a decrease was associated with the other two. The changes were permanent, and therefore not likely due to the flare emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 42 publications
7
82
0
Order By: Relevance
“…The sign of this change remains inconclusive, however, since both, an increase of the shear (Wang 1992;Chen et al 1994;Wang et al 1994Wang et al , 2012aLiu et al 2005;Petrie 2012), as well as a decrease has been found during flares (Wang 2006). To explain such contradictory results, Dun et al (2007) proposed that the measures for the non-potentiality of a magnetic field may take on different values from one portion of an AR to another.…”
Section: Coronal Implosion and Photospheric Responsementioning
confidence: 99%
“…The sign of this change remains inconclusive, however, since both, an increase of the shear (Wang 1992;Chen et al 1994;Wang et al 1994Wang et al , 2012aLiu et al 2005;Petrie 2012), as well as a decrease has been found during flares (Wang 2006). To explain such contradictory results, Dun et al (2007) proposed that the measures for the non-potentiality of a magnetic field may take on different values from one portion of an AR to another.…”
Section: Coronal Implosion and Photospheric Responsementioning
confidence: 99%
“…In the early time, most observations focused on the photospheric magnetic-field changes in the course of major flares, such as the magnetic shear changes along the flaring polarity inversion lines (PILs; Ambastha et al 1993;Chen et al 1994;Hagyard et al 1999), the stepwise changes in the longitudinal fields (Kosovichev & Zharkova 2001;Sudol & Harvey 2005), and so on. When these observations concluded that the longitudinal field flux variations were unbalanced between the disk-and limb-ward Wang et al 2002;Yurchyshyn et al 2004;Wang 2006), the white-light sunspot structure changes during major flares were also identified, which found that the penumbrae often became darker close to the central PILs while they decayed in the peripheral region Deng et al 2005;Liu et al 2005;Chen et al 2007). In more recent years, high-resolution white-light sunspot observations revealed some changes in photospheric fine structures caused by flares, e.g., disappearing penumbra fibrils and transition bright grains could evolve into faculae (Wang et al 2012a), granulation pattern could evolve to alternating dark and bright penumbra fibril structures (Wang et al 2013), and there were remarkable high-speed flows along the flaring PILs (Shimizu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This standard method may not necessarily reflect the correct amount of maximum free energy released during a solar flare, since the magnetic field in the photospheric boundary B(x, y, z phot ) may change during a flare (e.g., see measurements by Wang et al, 1994Wang et al, , 2002Wang et al, , 2013Wang, 1997Wang, , 2006Wang and Liu, 2010). Another problem with NLFFF codes using the photospheric vector field is the non-force-freeness of the lower chromosphere (Metcalf et al, 1995;DeRosa et al, 2009), which however, can be ameliorated by preprocessing the magnetic boundary data, using chromospheric field measurements (e.g., Metcalf et al, 2005;Jing et al, 2010), or by a multigrid optimization that minimizes a joint measure of the normalized Lorentz force and the divergence of the magnetic field, as proposed by Wiegelmann (2004) and applied by Jing et al, (2009).…”
Section: Introductionmentioning
confidence: 99%